A novel synthesis of nanoflower-like zinc borate from zinc oxide at room temperature - Vu T Tan; La The Vinh; Le Tu Quynh; Huynh Thu Suong; Huynh Dang Chinh (Materials Research Express, 2020)
For the first time, the nanoflower-like zinc borate compound was obtained by precipitation at room temperature using zinc oxide nanoparticles as a precursor. The obtained zinc borates were characterized by Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), x-ray diffraction (XRD), thermal gravimetric analysis (TGA), and Raman spectroscopy analysis. Monoclinic of zinc borate 2ZnO. 3B _2 O _3 .3.5H _2 O was achieved under the XRD pattern and the elemental chemical analysis. The particle size of the obtained materials is approximately 5 nm using TEM analysis. The TGA shows that the achieved zinc borate is outstanding stable at high temperatures. The result of this work provides a new route for the fabrication of zinc borate nanoparticle, which could be widely used in many applications.